THE INFLUENCE OF CORPORATE GOVERNANCE MECHANISM ON EARNINGS MANAGEMENT - Maria Mulianita Sunata; Melinda Haryanto (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2019)
This research aims to study the relationship between corporate governance mechanism and earnings management. Corporate governance, proxied by institutional ownership and managerial ownership are the mechanism that is expected to reduce this practice by minimizing the agency problem. Earnings management is proxied by absolute discretionary accruals. Control variables are used in this research are company size, Return on Assets and Leverage. The number of samples used in this research is 70 manufacturing companies which are listed in Indonesia Stock Exchange during three consecutive years 2014-2016, therefore the number of sample companies used during three years is 210. These companies are selected by using purposive sampling technique. The analysis method used in this research is multiple linear regression analysis. The conclusions based on the results indicate that institutional ownership and managerial ownership have negative not significant influence on earnings management, control variables company size has negative significant influence on earnings management, return on assets has positive significant influence on earnings management, and leverage has positive not significant influence on earnings management. Keywords: Earnings Management, Corporate Governance Mechanism, Company Size, Financial Performance